Working Hour and its Impact on Backache from Gender Perspective - Pradhan, Amita; Shrestha, Neera (Dhaulagiri Journal of Sociology and Anthropology, 2011)
This paper aims to analyze the association between work burden and backache among women and men. The study design is descriptive cross sectional. Thirty two households are selected. From each of the households sample size of 64 in terms of a pair of either married couple or the unmarried sister and brother are selected. Respondent's age is between 15 to 49 years. Semi structured questionnaire is used to collect data. This study shows significant differences in working hour between male and female. The working hour is significantly higher among the persons with backache. Gender inequality is a stark reality. The gender division of labour may add more work to women resulting into longer working hour for women. This may reflect in some health hazards among women. Hence, more focused attention is needed to understand the non reproductive health problems of women. Keywords: working hour; backache; women empowerment; health problem; health seeking behaviour DOI: 10.3126/dsaj.v4i0.4523 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.235-246